HDAC2‐Mediated METTL3 Delactylation Promotes DNA Damage Repair and Chemotherapy Resistance in Triple‐Negative Breast Cancer - Xiaoniu He; Yuanpei Li; Jian Li; Yu Li; Sijie Chen; Xia Yan; Zhangrong Xie; Jiangfeng Du; Guoan Chen; Jianbo Song; Qi Mei (Advanced Science)
Abstract The current treatment of triple‐negative breast cancer (TNBC) is still primarily based on platinum‐based chemotherapy. However, TNBC cells frequently develop resistance to platinum and experience relapse after drug withdrawal. It is crucial to specifically target and eliminate cisplatin‐tolerant cells after platinum administration. Here, it is reported that upregulated N 6‐methyladenosine (m6A) modification drives the development of resistance in TNBC cells during cisplatin treatment. Mechanistically, histone deacetylase 2 (HDAC2) mediates delactylation of methyltransferase‐like 3 (METTL3), facilitating METTL3 interaction with Wilms’‐tumor‐1‐associated protein and subsequently increasing m6A of transcript‐associated DNA damage repair. This ultimately promotes cell survival under cisplatin. Furthermore, pharmacological inhibition of HDAC2 using Tucidinostat can enhance the sensitivity of TNBC cells to cisplatin therapy. This study not only elucidates the biological function of lactylated METTL3 in tumor cells but also highlights its negative regulatory effect on cisplatin resistance. Additionally, it underscores the nonclassical functional mechanism of Tucidinostat as a HDAC inhibitor for improving the efficacy of cisplatin against TNBC.